Finitary and Artinian-Finitary Groups over the Integers ℤ - Wehrfritz, B.A.F. (Український математичний журнал, 2002)
In a series of papers, we have considered finitary (that is, Noetherian-finitary) and Artinian-finitary groups of automorphisms of arbitrary modules over arbitrary rings. The structural conclusions for these two classes of groups are really very similar, especially over commutative rings. The question arises of the extent to which each class is a subclass of the other.

Here we resolve this question by concentrating just on the ground ring of the integers ℤ. We show that even over ℤ neither of these two classes of groups is contained in the other. On the other hand, we show how each group in either class can be built out of groups in the other class. This latter fact helps to explain the structural similarity of the groups in the two classes. У низці робіт автора розглядались фінітарні (іобто нетерово-фінітарні) і аргипово-фінітарні групи автоморфізмів довільних модулів над довільними кільцями. Структурні висновки для цих двох класів груп дуже подібні, особливо у випадку комутативних кілець. Виникає питання про те, в якій мірі один з цих класів є підкласом іншого.
У даній роботі цс питання вирішується па прикладі кільця чисел ℤ. Показано, що навіть для ℤ жоден із цих двох класів не міститься в іншому. З іншого боку, показано, як будь-яку групу одного класу можна побудувати з груп іншого, що дає можливість пояснити структурну подібність груп в цих двох класах.